Pengaruh Model Pembelajaran Berbasis Masalah Terhadap Hasil Belajar Matematika pada Siswa Kelas IV di SD Negeri 39 Cakranegara - Fahrezi, Aldy; Fauzi, Asri; Handika, Ilham (Mataram University, 2025)
This study aims to examine the effect of the Problem-Based Learning Model on mathematics learning outcomes in fourth-grade students at SD Negeri 39 Cakranegara. The method used was a quasi-experiment by dividing the sample into two groups, namely the control class (28 students) who received conventional learning and the experimental class (28 students) who were intervened using the PBL model. Data collection was conducted through cognitive written tests and analyzed using an independent sample t-test. The results showed that the application of PBL significantly improved student learning outcomes, as indicated by the higher posttest average score of the experimental class (82.28) compared to the control class (77.33). The statistical test also obtained a significance value of 0.039 (< 0.05), which reinforced the acceptance of the alternative hypothesis. The conclusion of this study is that the Problem-Based Learning Model is proven to be effective and significantly relevant in improving academic learning outcomes while fostering important skills such as critical thinking, creativity, and collaboration in elementary school students.